Antihypertensive therapy in renal patients - Schwenger, Vedat; Zeier, Martin; Ritz, Eberhard (Nephron, 1999)
High blood pressure values, diastolic and systolic, are associated with decreased renal function. This is particularly true when the diastolic blood pressure is higher than 90 mm Hg. Several studies showed that lowering of the blood pressure within the range of normotension according to the WHO causes a reduction in the rate of progression to terminal renal failure. These studies have led to recommendations to aim at a target blood pressure of approximately 125/75 mm Hg in the treatment of patients with glomerular diseases and particularly diabetic nephropathy with proteinuria >1 g/day. In contrast to these results, blood pressure values corresponding to the recommendation (≤125/75 mm Hg) of the JNC VI (see text) were achieved in 15% of the patients only. It has also been shown that at any given level of an average 24-hour blood pressure, patients with an insufficient decrease of the blood pressure during nighttime have a higher risk to progress to terminal renal failure. Thus it is very important to lower the nighttime blood pressure and to detect nighttime blood pressure increases using ambulatory blood pressure measurements.
Gesehen am 18.06.2021